Bridging the gap: Fostering high school students’ interest in civil engineering through an innovative introduction program - Yuwono, Bambang Endro; Misshuari, Imas Wihdah; Zayadi, Ruwaida; Inavonna, Inavonna; Adiyanto, Moch Rifky; Wibawa, Ilham Akbar Mulya (Universitas Muhammadiyah Magelang, 2025)
The low interest of high school students in civil engineering is a concern, as this field is crucial for infrastructure development. This community engagement program aimed to enhance the interest and understanding of civil engineering among students at SMAN 78 Jakarta through an innovative introductory program. The methods employed included interactive presentations on civil engineering, discussions, Q&A sessions, and evaluations. The results showed that 100% of students expressed a desire to learn more about civil engineering through follow-up activities, and 76.9% of students reported a better understanding of the field compared to before. Furthermore, 65.4% of students demonstrated increased interest in civil engineering, although the majority still placed it as a second or lower-choice major. The implications of this community service activity are increased awareness and interest among students in the field of civil engineering. However, to achieve a more significant shift in major selection, a more comprehensive approach is needed, such as more intensive career guidance, direct involvement with professionals, and more realistic work simulations.